The problems of energy supply of the Russian Arctic remote territories - Solovyev, Dmitry; Shilova, Lyubov; Gulev, Sergey (project baikal, 2023)
The article deals with the problems of energy supply of the Russian Arctic remote territories inhabited, among others, by indigenous and small-numbered peoples. Taking into account the electricity, heat and fresh water shortage, as well as climate change, the authors consider the possibilities of using new technologies for creating local infrastructure facilities of renewable energy sources (RES) integrated into the conditions of the traditional way of life for the formation of a favorable habitat in harmony with nature.
Keywords: energy resources; indigenous peoples of the North; habitat; RES